2021
DOI: 10.3390/v13112238
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and Evolution of SARS-CoV-2 in India: Let the Data Speak

Abstract: The COVID-19 pandemic is a global challenge that impacted 200+ countries. India ranks in the second and third positions in terms of number of reported cases and deaths. Being a populous country with densely packed cities, SARS-CoV-2 spread exponentially. India sequenced ≈0.14% isolates from confirmed cases for pandemic surveillance and contributed ≈1.58% of complete genomes sequenced globally. This study was designed to map the circulating lineage diversity and to understand the evolution of SARS-CoV-2 in Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Also, the mutation S194L found in the Nucleocapsid gene was a highly significant mutation observed across our cohort and is also associated with mortality. Several other studies have also reported that this mutation is deleterious and correlated with fatal outcomes ( Limaye et al., 2021 ; Mehta et al., 2021 ; SeyedAlinaghi et al., 2021 ). This could possibly indicate their crucial role in elevating the pathogenicity of the virus, thereby contributing to increased disease severity and clinical outcome.…”
Section: Discussionmentioning
confidence: 84%
“…Also, the mutation S194L found in the Nucleocapsid gene was a highly significant mutation observed across our cohort and is also associated with mortality. Several other studies have also reported that this mutation is deleterious and correlated with fatal outcomes ( Limaye et al., 2021 ; Mehta et al., 2021 ; SeyedAlinaghi et al., 2021 ). This could possibly indicate their crucial role in elevating the pathogenicity of the virus, thereby contributing to increased disease severity and clinical outcome.…”
Section: Discussionmentioning
confidence: 84%
“…Her group has developed novel algorithms for epitope predictions [57], alignment-free phylogeny and designed servers for virus tying [58][59][60]. She has active collaborations with national and international virologists and has worked towards investigating virus outbreaks and pandemics including COVID-19 [61][62][63]. With a focus on translation, Urmila has contributed to computational vaccine design (JEV, HPV16), to explain the escape of viruses from vaccine-induced neutralization (Mumps) and to understand potential impact of virus-host variations on efficacy of vaccine (COVID- 19).…”
Section: Dr Urmila Kulkarni-kale: Virus Evolution Diversification And...mentioning
confidence: 99%
“…A possible reason why the Indian subcontinent was so dramatically affected may have been the high prevalence of the A97V (SNP: C13730T) and P323L (SNP: C14408T) mutations in the RNA-dependent RNA polymerase (NSP12) on the subcontinent [39]. Both substitutions correlate with an approximately 100-fold higher evolution rate in India (6,73 x 10 -2 substitutions/site/year) compared to the global average (6,50 x 10 -4 substitutions/site/year) [41].…”
Section: Dominant Lineages With Fixed Snpsmentioning
confidence: 99%